Metal contamination in household dust and their health risk assessment: A study in two Malaysian cities - Lim, Xin Yi; Lye, Ting Fang; Tay, Joo Hui (Environmental Research Institute, Chulalongkorn University, Thailand, 2024)
Investigating the composition of household dust can provide crucial insights into potential environmental and health implications. This study aimed to determine the concentration of selected metals in 30 household floor dust samples collected from two cities in Peninsular Malaysia, namely Melaka and Butterworth. The samples were collected using nylon socks attached to a vacuum cleaner nozzle during January-February 2021. All samples were sieved through a 200-µm sieve, acid-digested with aqua regia, and analyzed using inductively coupled plasma mass spectrometry (ICP-MS). Mean metal concentrations decreased in the order of Fe>Al>Mg>Zn>Mn>Ba>Cu>Cr>Pb. Cd was not detected in any samples. The median concentrations of Al, Ba, and Mg from Melaka were significantly higher than those from Butterworth. Hazard indexes for all metals were less than one, indicating a low noncarcinogenic risk of exposure to occupants via inhalation, dust ingestion, and skin absorption. Statistical analyses revealed that the levels of metals in household dust were influenced by factors such as the location and age of the house, the presence of air conditioning, and the time since the last paint. This study highlights the presence of metals in indoor settings of different cities in Malaysia, providing fundamental data for future research in the field.